2021
DOI: 10.4049/jimmunol.2000780
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Graft-versus-Host Disease by Exopolysaccharide from a Commensal Bacterium

Abstract: Acute graft-versus-host disease (aGvHD) is a severe, often lethal, complication of hematopoietic stem cell transplantation, and although prophylactic regimens are given as standard pretransplantation therapy, up to 60% of these patients develop aGvHD, and require additional immunosuppressive intervention. We treated mice with a purified probiotic molecule, exopolysaccharide (EPS) from Bacillus subtilis, shortly before and after induction of aGvHD and found that, whereas only 10% of control mice survived to day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…To characterize global changes in inflammasome activation during aging, we used caspase-1 reporter mice described previously to visualize caspase-1 activation in vivo and ex vivo (37, 40, 41, 43). At ∼18 months of age, mice exhibited increased biosensor activation in vivo ( Fig 1A-B ), consistent with age-dependent increase in low-grade systemic inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize global changes in inflammasome activation during aging, we used caspase-1 reporter mice described previously to visualize caspase-1 activation in vivo and ex vivo (37, 40, 41, 43). At ∼18 months of age, mice exhibited increased biosensor activation in vivo ( Fig 1A-B ), consistent with age-dependent increase in low-grade systemic inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize global and tissue-specific changes in inflammasome activation during the process of aging, we utilized a transgenic mouse model in which a luciferase-based caspase-1 biosensor is constitively expressed in all tissues (37). Proteolytic activation of caspase-1 thus induces luciferase activation in specific tissues, allowing inflammasome activation to be monitored in vivo and ex vivo (37)(38)(39)(40)(41)(42)(43). These studies reveal a tissue-specific degree of overlap or discordance between age-associated inflammasome activation and upregulation of inflammatory transcripts commonly associated with inflammaging.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-1 is active in allogeneic CD4 + and CD8 + T cells in mice with aGvHD A number of groups have observed irradiation-induced inflammasome/inflammatory caspase activation in recipient tissues in mice [15][16][17] and in patients with severe GvHD [15], although there has been little investigation into the contribution of inflammatory caspase activation in alloreactive T cells, the cells driving pathology in this disease. Our previous data suggested that inflammatory caspases were active in allogeneic splenocytes [10,11]. To interrogate this further, we used the C57Bl/6 (H-2Kb) → BALB/c (H-2Kd) MHC major mismatched model of aGvHD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of these studies fail to account for the existence of numerous inflammasome receptors, many of which are poorly characterized, as well as the redundant roles of caspases as inflammasome effectors. Our previous results suggested that inflammatory caspase activation occurs in donor splenocytes in a model of aGvHD [ 10 , 11 ]. Here, we demonstrate activation of caspase-1 in alloreactive T cells using mouse and human models of aGvHD.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models, the administration of exopolysaccharide derived from Bacillus subtilis ameliorated aGvHD improving GvHD related mortality. This effect was mediated by the induction of inhibitory dentritic cells in a TLR4-dependent manner (105). SCFAs are the most investigated, and they represent a effector route in common with prebiotic compounds.…”
Section: Synbiotics and Post-bioticsmentioning
confidence: 99%